Economic Governance of Property Rights: comparative analysis on the collection of royalties in genetically modified soybean seeds - Monteiro, Guilherme Fowler de Avila; Zylbersztajn, Decio (Revista de Economia e Sociologia Rural (RESR), 2013)
This paper examines the governance of property rights on genetically modified (GM) soybean seeds. Specifically, the article undertakes a comparative analysis on the collection of royalties in GM soybean seeds in the U.S. and Brazil. For each country, the authors describe the regulatory framework governing the protection of biotechnology innovations in agriculture and investigate the mechanisms of royalty collection in GM soybean seeds. The paper also offers econometric evidence linking the capture of value on biotech innovations and the protection mechanisms deployed by biotech firms. The results suggest that, subject to the institutional environment, firms may choose to transact a GM attribute separated from the seed, building specialized governance structures framed around the genetic attribute and not around the seed as a whole.